novel radial self-rectifying air turbine for use in wave energy converters. Part 2. Results from model testing - Falcão, A.F.O; Gato, L.M.C; Nunes, E.P.A.S (Renewable energy, 2013)
The paper presents results from model testing of a self-rectifying radial-flow air turbine, that is being developed as an alternative to the axial-flow self-rectifying turbines for applications in wave energy conversion. In the new machine, named biradial turbine, the flow into, and out of, the rotor is radial. The rotor is surrounded by a pair of radial-flow guide-vane rows. The downstream guide vanes are prevented from obstructing the flow coming out of the rotor by axially displacing the whole guide vane set. The turbine model, with a 0.488 m diameter rotor, was tested in unidirectional flow. Experimental results are shown, in dimensionless form, for efficiency, power and pressure head versus flow rate. They are compared with predictions from CFD computations. The results from model testing were used to estimate the time-averaged efficiency of the turbine subject to the irregular bidirectional air flow induced by random waves.